A Near-Infrared Light Triggered Composite Nanoplatform for Synergetic Therapy and Multimodal Tumor Imaging - Wu, Mingzhou; He, Shuqing; Hu, Xin; Chen, Jingqin; Ha, Enna; Ai, Fujin; Ji, Tao; Hu, Junqing; Ruan, Shuangchen (Frontiers in Chemistry, 2021)
Transition-metal chalcogenide compounds with facile preparation and multifunctional elements act as ideal photothermal agents for cancer theranostics. This work synthesizes Cu7.2S4/5MoS2 composite nanoflowers and investigates the crystal growth mechanism to optimize the synthesis strategy and obtain excellent photothermal therapy agents. Cu7.2S4/5MoS2 exhibits a high photothermal conversion efficiency of 58.7% and acts as a theranostic nanoplatform and demonstrated an effective photothermal–chemodynamic–photodynamic synergetic therapeutic effect in both in vitro and in vivo tests. Moreover, Cu7.2S4/5MoS2 shows strong photoacoustic signal amplitudes and computed tomographic contrast enhancement in vivo. These results suggest a potential application of Cu7.2S4/5MoS2 composite nanoflowers as photo/H2O2-responsive therapeutic agents against tumors.